A Preisach Model for Monotonic Tension Response of Structural Mild Steel with Damage - Knežević, Petar; Šumarac, Dragoslav; Perović, Zoran; Dolićanin, Ćemal; Burzić, Zijah (Periodica Polytechnica Civil Engineering, 2020)
This paper presents the new type of Preisach model that describes the elastoplastic behavior of structural mild steel under axial monotonic tension load with damage. Newly developed model takes into account elastic region, horizontal yield plateau, plastic hardening region, and softening region due to material damage under tension. In order to study the monotonic behavior of structural mild steel and find suitable material properties for the model, monotonic axial tensile tests up to the failure are carried out. Tests are conducted on specimens of the three most common types of European structural steel S235, S275, and S355. The basis of the model represents a mathematical description of material single crystal monotonic axial behavior. In the multilinear mechanical model, a drop in stress, after achieving ultimate stress under tension is achieved by a negative stiffness element. The good agreement with experimental results is accomplished by parallel connection of infinitely many single crystal elements, forming the polycrystalline model. The model represents a good solution for common engineering practice due to its geometrical representation in form of Preisach triangle.